Defining and Characterizing Women Entrepreneurship - Sorin-George Toma (Ovidius University Annals: Economic Sciences Series)
Entrepreneurship plays a key role in sustaining economic development, ensuring economic growth, launching innovative products and/or services, and satisfying social needs of communities and/or societies. Last decades have witnessed the rapid development of women entrepreneurship all over the world. As women have been increasingly involved in business startup since the beginning of the 21st century, the number of women entrepreneurs has soared in most countries of the world. The paper aims to briefly define and characterize women entrepreneurship. To attain the purpose of the paper the author used a qualitative scientific research method. The paper contributes to the expansion of the scientific literature regarding women entrepreneurship. It analyses various definitions and identifies several main characteristics of women entrepreneurship.